Perovskite Solar Cells: Alkali Chlorides for the Suppression of the Interfacial Recombination in Inverted Planar Perovskite Solar Cells (Adv. Energy Mater. 19/2019). Issue 19 (16th May 2019) - Chen, Wei; Zhou, Yecheng; Chen, Guocong; Wu, Yinghui; Tu, Bao; Liu, Fang‐Zhou; Huang, Li; Ng, Alan Man Ching; Djurišić, Aleksandra B.; He, Zhubing
Abstract : In article number1803872, Aleksandra B. Djurišić, Zhubing He and co‐workers report a promising inverted planar perovskite solar cell using NiO as the hole‐transport‐layer. Significant suppression of interfacial recombination is achieved by a facile alkali chloride modification at the interface between NiO and perovskite. This modification induces the ordering of the perovskite crystal and in turn decreases its defect/trap density, hence reducing interfacial recombination and augmenting the device open‐circuit voltage significantly.